Basic thermodynamics to save lives. (3rd July 2021) - Thiam, Mouhamadou
Abstract: Students have several misconceptions about thermodynamics. However, an understanding of basic concepts in this branch of physics remains fundamental to explain thermal phenomena. The purpose of this activity was to extend students' conceptual understanding of heat, temperature, energy, and thermal insulators and conductors. Two groups of students in grade seven created insulation boxes to keep sheep organs in a hypothermic state for the longest time possible. The activity incorporated connections to real life, autonomy, and scientific investigations to motivate the students. The data indicated that the activity was sufficiently challenging for the students and that they were able to apply their understanding of both the corresponding concepts and scientific and engineering practices. Supplemental data for this article is available online at at [publisher's weblink].